التعليم العالي في الوطن العربي: الواقع والتصورات المستقبلية - ابراهيم خليف العلاف (PROSPECTIVE RESEARCHES, 2023)
Universities in our contemporary world have no longer being a field of teaching only but also expanded in its functions to be centers scientific research, developing learning and planning for the future towards creating a stabled scientific base in the society. As far as, modern higher education is concerned whether the official one or the private one in the Arab Homeland, its age is not long with regard to the well-known university institutions in the advanced world. This paper is merely an attempt to stand upon the initial roots of its existence. Knowing its present reality, its joint characteristics, aspects of criticism directed against it from intellectuals, educators and others who are interested in its future and its capability to participate in the economic, social and cultural change. Also, this paper spots light upon knowing the possibility of developing private education institutions (the paralleled) to be supporters for the official higher education institutions.